High Frequency Trading and the New-Market Makers - Albert J. Menkveld (Tinbergen Institute, 2011)
This paper links the recent fragmentation in equity trading to high frequency traders (HFTs). It shows how the success of a new market, Chi-X, critically depended on the participation of a large HFT who acts as a modern market-maker. The HFT, in turn, benefits from low fees in the entrant market, but also uses the incumbent market Euronext to offload nonzero positions. It trades, on average, 1397 times per stock per day in Dutch index stocks. The gross profit per trade is exteuroO.88 which is the result of a exteuro1.55 profit on the spread net of fees and a exteuroO.68 'positioning' loss. This loss decomposes into a exteuro0.45 profit on positions of less than five seconds, but a loss of exteuro1.13 on longer duration positions. The realized maximum capital commit- ted due to margin requirements is exteuro2.052 million per stock which implies an annualized Sharpe ratio of 9.35.
Keywords: G10; 330; high-frequency trading; market maker; multiple markets